Multiplatform Application Technology – Based Heutagogy on Learning Batik: A Curriculum Development Framework - Widiaty, Isma; Riza, Lala Septem; Abdullah, Ade Gafar; Mubaroq, Sugeng Rifqi (Universitas Pendidikan Indonesia, 2020)
This study aimed to design a batik learning medium for vocational high school students in based on multiplatform. The application made was expected to support heutagogy approach – based learning and to deal with the development of science and technology integrated in the curriculum of vocational high schools. The application developed, namely e-botik, was an integration of several previously-designed applications using Code ignitor (CI) framework. The database used was My-SQL. It is commonly known that Code igniter is an open source web application framework utilized to create dynamic PHP applications. In this study, e-botik consisted of three main components including interface, database, and application programming interface (API). Some of the applications combined were ARtikon_joyful (Android-based), Video Kasumedangan Batik (movie player), Nalungtik Batik (desktop-based), Digi_Learnik (web-based), Batik UPI (manual), Batik Cireundeu (manual), and Lembar Balik (manual). The combination proceeded web-based so that it was compatible with various operating systems. The application (e-botik) was designed and then tested. The test was performed through whitebox testing and blackbox testing. The results of the test showed that it ran well and was able to be used a batik learning media. It is expected that students can utilize e-botik in selecting topics of learning batik in accordance with their competences and needs. This condition enables e-botik to support learning batik through heutagogical approach. In addition, the application was also validated in terms of both system and usage aspects.